THE IMPORTANCE OF CUSTOMER VALUE AND LUXURY VALUE PERCEPTION : IMPLICATIONS FOR MASSTIGE LUXURY BRANDS - Ghimire, Kunjan (My University, 2018)
With the rise in competition and demanding customers, luxury brands are compelled to look for ways to compete on providing superior customer value delivery. Superior customer value increases customer satisfaction and customer retention. Past studies have largely looked at traditional luxury brands, which makes it worthwhile to study the newer concept on luxury, represented by masstige luxury brands. The research aims to provide the implications of luxury value perceptions within the Indian market for masstige luxury brands. To do so, it compares the customers’ desired values with received values from masstige brands. The three sub-questions include: 1) What are the image value dimensions received from masstige luxury brands. 2) Which value dimensions play important role in luxury value perception. 3) How well (poorly) does the masstige brands delivered/received value align with desired value dimensions. Quantitative methods were used to collect the data. The study incorporated mall-intercept survey as data collection technique. The Statistical Package for the Social Sciences (SPSS) version 22.00 was used for data analysis. Data analysis techniques used in the study were analysis of frequencies, reliability analysis, and factor analysis. The findings suggest that the desired luxury value dimensions does not align with the received value dimensions of masstige brands. The implications to masstige brand is to design their marketing efforts to increase the status and other directed value. The brands should try to convey the message that these brands hold higher value and impress others. Masstige brands should reconsider directing their resources and marketing strategies from less relevant value dimensions (functional, hedonic, and self-directed value dimensions to more important value dimensions (other-directed and cost/sacrifice value dimension).
Keywords: Customer value, Customer value determination, Masstige luxury brands, luxury value perception